Multiple signaling pathways convey central and peripheral signals to regulate pituitary function: Lessons from human and non-human primate models. (5th March 2018) - Vázquez-Borrego, M.C.; Gahete, M.D.; Martínez-Fuentes, A.J.; Fuentes-Fayos, A.C.; Castaño, J.P.; Kineman, R.D.; Luque, R.M.
Abstract: The anterior pituitary gland is a key organ involved in the control of multiple physiological functions including growth, reproduction, metabolism and stress. These functions are controlled by five distinct hormone-producing pituitary cell types that produce growth hormone (somatotropes), prolactin (lactotropes), adrenocorticotropin (corticotropes), thyrotropin (thyrotropes) and follicle stimulating hormone/luteinizing hormone (gonadotropes). Classically, the synthesis and release of pituitary hormones was thought to be primarily regulated by central (neuroendocrine) signals. However, it is now becoming apparent that factors produced by pituitary hormone targets (endocrine and non-endocrine organs) can feedback directly to the pituitary to adjust pituitary hormone synthesis and release. Therefore, pituitary cells serve as sensors to integrate central and peripheral signals in order to fine-tune whole-body homeostasis, although it is clear that pituitary cell regulation is species-, age- and sex-dependent. The purpose of this review is to provide a comprehensive, general overview of our current knowledge of both central and peripheral regulators of pituitary cell function and associated intracellular mechanisms, focusing on human and non-human primates. Highlights: Pituitary gland is an essential regulator of multiple physiological functions. Pituitary serve as a metabolic sensor to integrate central and peripheral signals. The control of pituitary function is far more complex than originally envisioned. Multiple signaling pathways are involved in the regulation of pituitary function. This review highlights what we know about the pituitary control in humans/primates.